The implications of sugarcane contract farming on land rights, labor, and food security in the Bunyoro sub-region, Uganda. (November 2022) - Bahati, Ibrahim; Martiniello, Giuliano; Abebe, Gumataw Kifle
Abstract: Over the years, the Ugandan government had been promoting agricultural commercialization to become a middle-income economy by 2020. In 2012, the president remarked that if all the 40 million acres of arable land were put to full potential, everyone would be richer. Sugarcane commercialization, in the form of contract farming, has been praised as one of the preferred instruments to promote it, leading to the emergence of large and medium sugar corporations in Uganda's countryside. The study aims to provide insights into the commercialization process of smallholder agriculture through sugarcane contract farming (CF) and the implications on land rights, labor relations, and rural livelihoods, taking Uganda's Bunyoro sub-region as a case. To achieve this objective, the study used a qualitative approach and carried out in-depth interviews with a total of 75 participants who were directly affected by the actions of the sugar production and or participated in the CF scheme (as outgrowers) as well as factory officials. The findings highlight that the wave of CF schemes around sugar, which was engineered by a convergence of power and interest between the Ugandan state and Indian capital investments, adversely integrates rural farmers into sugar commodity production networks amidst unequal contractual relations, expanding agro-extractivist search for cheap land and labor rather than bringing inclusive rural development. Highlights: How sugar contract farming is impacting rural livelihoods in Uganda. Sugar contract farming and food security in Uganda. The impact of sugar contract farming on land rights, labor, and other socioeconomic relations in the Bunyoro-subregion. The process of commercial sugarcane farming in rural development praxis in Africa. How neoliberalism influences agribusiness and agricultural policy in Africa.